The Potential of Teledentistry as an Effort to Expand Dental and Oral Health Services in Indonesia - FILGAZWI, Azbara; PELENGKAHU, Muhammad Rahjay (Community Services: Sustainability Development, 2023)
Health concerns in Indonesia continue to be a significant obstacle for the government in meeting the public's demand for quality health services. Particularly with regard to oral health and dental services. This research is a literature review in which descriptive-qualitative analysis methods were applied to the consulted sources. The reference materials utilized in this study are sourced from a variety of credible and pertinent publications, in accordance with the subject matter. The findings of this research indicate that the present level of health service coverage in Indonesia is suboptimal. Thus, a significant number of Indonesians continue to lack access to oral health and dental care. Obviously, the government, in this instance the Ministry of Health, must evaluate its performance in ensuring that all regions of the country have access to health services. A national teledentistry practice might serve as an alternative solution to this issue. The implementation of teledentistry in Indonesia is highly promising, notwithstanding the numerous obstacles that are present in the country